Determinants of Corporate Climate Change Disclosure for European Firms. (12th October 2017) - Giannarakis, Grigoris; Zafeiriou, Eleni; Arabatzis, Garyfallos; Partalidou, Xanthi
Abstract: This study identifies the determinants of climate change disclosure under the prism of sustainable development in European context. The selected variables involve environmental performance, ownership structure, and verification of climate change initiatives. Cross‐sectional data derived from the Bloomberg terminal of the European 500 index concerning 215 firms in the year 2014 are employed. The novelty of the present study stands on the use of proxies for climate change disclosure by adopting the Climate Performance Leadership Index (CPLI). The results reveal that better environmental performance positively affects the level of climate change disclosure. In addition, governmental ownership and independent verification of environmental data determine climate change disclosure. Thus, climate change disclosure is thought to be an effective managerial tool for shareholders and stakeholders to superintend corporate management limiting information asymmetry level; furthermore, higher environmental performers prefer actual climate change disclosure providing a plausible signal. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment